Evaluation of COBAS AMPLICOR (Roche): Accuracy in Detection of Chlamydia trachomatis and Neisseria gonorrhoeae by Coamplification of Endocervical Specimens - Livengood, Charles H. (American Society for Microbiology, 2001)
We evaluated further the accuracy of the COBAS AMPLICOR (Roche) (CA) PCR-based system in detection of Chlamydia trachomatis and Neisseria gonorrhoeae in endocervical specimens. Endocervical specimens collected for any indication for testing for C. trachomatis and N. gonorrhoeae among a university hospital health system population were included. Testing for C. trachomatis was done by two PCR methods, CA and manual microwell AMPLICOR (Roche) (MWA), and by culture; testing for N. gonorrhoeae was done by CA and culture. Discrepancy resolution was performed. Reproducibility testing and hands-on labor time measurements for CA were done. Among 654 C. trachomatis samples, the prevalence of true positivity was 9.2%, and among the 618 N. gonorrhoeae samples, the prevalence of true positivity was 4.4%. For detection of C. trachomatis, the sensitivity, specificity, and negative and positive predictive values were, respectively, as follows for each test: CA, 93.3, 99.7, 99.3, and 96.4%; MWA, 91.7, 99.7, 99.2, and 96.5%; and culture, 65.0, 100, 96.6, and 100%. For detection of N. gonorrhoeae those values were as follows: CA, 96.3, 100, 99.8, and 100%; and culture, 92.6, 100, 99.7, and 100%. Hands-on labor time for each clinical result was estimated to be at 7.5 min. The prevalence of inhibitory specimens was 3.5%, including two positive C. trachomatis samples which would have been missed otherwise. The direct cost of each clinical result with CA was estimated to be $9.09. Our methods include a diverse range of indications for testing among women, using endocervical swabbing samples, 2 M sucrose phosphate transport medium, and discrepancy resolution for comparison. Under our test conditions, the CA system is an accurate, rapid, and cost- and labor-efficient method for detection of C. trachomatis and N. gonorrhoeae.